Targeting N-type calcium channels in young-onset of some neurological diseases - Antunes, Flavia Tasmin Techera; De Souza, Alessandra Hubner; Figueira, Juliana; Binda, Nancy Scardua; Carvalho, Vanice Paula Ricardo; Vieira, Luciene Bruno; Gomez, Marcus Vinícius (Frontiers in Cell and Developmental Biology, 2022)
Calcium (Ca 2+) is an important second messenger in charge of many critical processes in the central nervous system (CNS), including membrane excitability, neurotransmission, learning, memory, cell proliferation, and apoptosis. In this way, the voltage-gated calcium channels (VGCCs) act as a key supply for Ca2+ entry into the cytoplasm and organelles. Importantly, the dysregulation of these channels has been reported in many neurological diseases of young-onset, with associated genetic factors, such as migraine, multiple sclerosis, and Huntington’s disease. Notably, the literature has pointed to the role of N-type Ca2+ channels (NTCCs) in controlling a variety of processes, including pain, inflammation, and excitotoxicity. Moreover, several Ca2+ channel blockers that are used for therapeutic purposes have been shown to act on the N-type channels. Therefore, this review provides an overview of the NTCCs in neurological disorders focusing mainly on Huntington’s disease, multiple sclerosis, and migraine. It will discuss possible strategies to generate novel therapeutic strategies.